A small-molecule activator induces ULK1-modulating autophagy-associated cell death in triple negative breast cancer. Issue 4 (3rd April 2017) - Ouyang, Liang; Zhang, Lan; Fu, Leilei; Liu, Bo
ABSTRACT: ULK1 (unc-51 like autophagy activating kinase 1) is well known to be required to initiate the macroautophagy/autophagy process, and thus activation of ULK1-modulating autophagy/autophagy-associated cell death (ACD) may be a possible therapeutic strategy in triple negative breast cancer (TNBC). Here, our integrated The Cancer Genome Atlas (TCGA) data set, tissue microarray-based analyses and multiple biologic evaluations together demonstrate a new small-molecule activator of ULK1 for better understanding of how ULK1, the mammalian homolog of yeast Atg1, as a potential drug target can regulate ACD by the ULK complex (ULK1-ATG13-RB1CC1/FIP200-ATG101), as well as other possible ULK1 interactors, including ATF3, RAD21 and CASP3/caspase3 in TNBC. Moreover, such new inspiring findings may help us discover that this activator of ULK1 (LYN-1604) with its anti-tumor activity and ACD-modulating mechanisms can be further exploited as a small-molecule candidate drug for future TNBC therapy.